A Developmental Disorder of Signed Language Production in a Native Deaf Signer of ASL - David Quinto-Pozos; Frances Cooley (Languages, 2020)
Evidence for a Developmental Language Disorder (DLD) could surface with language processing/comprehension, language production, or a combination of both. Whereas, various studies have described cases of DLD in signing deaf children, there exist few detailed examples of deaf children who exhibit production issues in the absence of processing or comprehension challenges or motor deficits. We describe such a situation by detailing a case study of “Gregory”, a deaf native signer of American Sign Language (ASL). We adopt a detailed case-study methodology for obtaining information from Gregory’s family and school, which we combine with linguistic and non-linguistic data that we collected through one-on-one sessions with Gregory. The results provide evidence of persistent issues with language production (in particular, atypical articulation of some phonological aspects of signs), yet typical comprehension skills and unremarkable fine-motor motor skills. We also provide a snapshot of Gregory’s rich linguistic environment, which we speculate, may serve to attenuate his production deficit. The results of this study have implications for the provision of language services for signing deaf children in schools and also for language therapists. We propose that language therapists who are fluent in signed language be trained to work with signing children.